Pengaruh Keragaman Produk Dan Kualitas Pelayanan Terhadap Minat Beli: Survei Pada Konsumen Toko Pakaian Area Singaparna Tasikmalaya - Panji Amanulloh; Ari Arisman; Barin Barlian (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study is to determine the effect of product diversity and service quality on consumer buying interest of Singaparna Area Clothing Store , Tasikmalaya Regency. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Singaparna Area Clothing Stores. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that product diversity and service quality have a significant effect both partially and simultaneously on consumer buying interest in Singaparna Tasikmalaya Area Clothing Stores.